Assessment of flexural behaviour of concrete beam with corroded steel rebar using acoustic emission technique / Ahmad Zaki - Ahmad , Zaki (2018)
Corrosion of reinforced concrete (RC) structures has been one of the major causes of structural failure. Early detection of the corrosion could help limit the location and the extent of necessary repair, as well as reduce the cost associated with rehabilitation work. Non-destructive testing (NDT) method has been found to be useful for corrosion assessments of civil infrastructures, where the effect of steel corrosion can be assessed effectively. The acoustic emission (AE) technique, one of the NDT methods, is more effective for assessing steel corrosion in the RC structures. The AE technique successfully monitors and analyse energy signals released from the fracture of the concrete matrix by steel corrosion activity using AE sensors placed on the concrete surfaces. The main objective of this study is to utilize the AE technique for flexural behaviour assessment of corroded RC beams under load testing. Three different types of experiment sets were performed for evaluation of corroded specimens using the AE technique. During the experiments, the corroded specimen was flexurally loaded together with data acquisition by AE technique. The data obtained were processed and AE parametric-based analysis was carried out. The first experiment was carried out subjected to monotonic loading by looking into the primary AE signals. Thereafter, based on the experience gained in the first experiment, the second and third experiments were utilized for small scales of corroded specimens subjected to cyclic load and monotonic loading, for secondary and primary AE signals, respectively. The second experiment was pre-corrosion beam specimens while the third experiment was post-corrosion beam specimens. The primary AE signal is typically due to changes of concrete material such as crack growth and fracture. The secondary AE signal is related to activity that was not part of original iv fabrication such as friction between the interface of steel reinforcement and concrete. The AE technique of the first experiment was successfully conducted for fracture mechanisms monitoring of the corroded specimen under flexure load. The RA value of AE parameters was used to evaluate the fracture mode in the corroded specimens. The Control and LC specimens exhibited the highest RA value at the final damage stage, however, the HC specimen exhibited the highest RA value at the damage stage 2. Therefore, the highest RA value was associated with the shear cracks which further explain that high intensity events occurred at the tension reinforcement area in the concrete. Moreover, the index of damage (ID) derived from the AE energy parameters obtained during the damage stage 1 was found to be useful as an indicator for evaluating the extent of corrosion damage of beam specimens at initial loadings. For the result of the second and third experiments, the primary AE parameters include the AE hits, RA value, AF, Ib-value, historic index (Hi), and severity index (Sr) of AE data were successfully introduced to assess the flexure behavior of the corroded beam specimen. For secondary AE, the cumulative signal strength (CSS) ratio of experiment 3 increases from 17.42 % to 116.22 % with the increase in corrosion level. It indicates that the occurrence of damage was generated due to loss in cross-section (mass loss) of the specimen before first visible crack occurs. The experiments conducted in this research helped to understand the flexural behavior of the corroded specimen under loading test using the AE technique. The secondary AE result of the second and third experiments were successfully found as the indicator of the damage occurrence of the corroded specimen at an early stage of the damage.